PERFEKSIONISME, HARGA DIRI, DAN KECENDERUNGAN DEPRESI PADA REMAJA AKHIR - Anindito Aditomo; Sofia Retnowati (Faculty of Psychology, Universitas Gadjah Mada, 2004)
The relations between perfectionism, self-esteem, and depression were examined among 77 normal subjects (late adolescence college students). Multiple regression analysis was conducted to test the hypothesis that general perfectionism and self-esteem played a significant role in depressive symptoms. In addition to the regression analysis, product moment analyses were conducted to determine the correlation of each of the five dimensions of perfectionism with depressive symptoms. Results indicated that general perfectionism and selfesteem were significant predictors of depressive symptoms. The regression model informs that general perfectionism (β= 0,143; p